Efficacy of paliperidone palmitate once-monthly (PP1M) in improving social functioning and reducing caregiver burden in patients with schizophrenia: a six-month follow-up study - Ling Dong; Xiao-Yan Liu; Wen-Cai Chen; Xiao-Xin Dong; Fan Wang; Si-Jing Chen; Xiu-Jun Liu (BMC Psychiatry)
Abstract Background Schizophrenia is a complex chronic mental disorder that severely impairs patients’ social functioning and quality of life, while imposing substantial burdens on families and society. Long-acting injectable antipsychotics (LAIs) have demonstrated potential advantages in improving both symptoms and social functioning. This study investigated the effects of transitioning from oral antipsychotics (OAPS) to Paliperidone Palmitate Once-Monthly (PP1M) on symptom control, social functioning, and caregiver burden in schizophrenia patients. Methods From April 11 to October 31, 2024, participants were assessed monthly using the Positive and Negative Syndrome Scale-6 (PANSS-6), Brief Psychiatric Rating Scale (BPRS), and adverse effect records. The Zarit Caregiver Burden Inventory and Personal and Social Performance (PSP) scale were administered biannually. Results Among 95 patients completing 6-month PP1M treatment, Zarit Burden scores decreased significantly by 44.89% (p < 0.001), while PSP scores increased by 8.60% (p = 0.001). Both PANSS-6 and BPRS total scores showed significant reductions (p < 0.00238). A moderate negative correlation was observed between BPRS improvement and PSP enhancement (r = -0.535, p < 0.001). Conclusion PP1M treatment effectively controlled symptoms, improved social functioning, and reduced caregiver burden in schizophrenia patients. The significant correlation between symptom improvement and functional recovery suggests PP1M may substantially support long-term rehabilitation and quality of life enhancement.